Pendampingan Komunitas Siswa dalam membangun Usaha Edupreneurship Halal di MAN 2 Tanjung Jabung Barat : Pengabdian - Dahlim, Muhammad; Nadiyah, Nadiyah; Syarif, Maryadi; Yuliana, Yuliana (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to enhance students’ understanding and basic skills in halal edupreunership through a one-hour session delivered by the speaker, Artiyanti, S.Kom, on Thursday, November 13, 2025, from 08:00 to 09:00 AM at MAN 2 Tanjung Jabung Barat. The activity was carried out in response to students’ need to comprehend halal entrepreneurship concepts and identify creative business opportunities within the madrasa environment. The implementation methods included interactive lectures, discussions, and simple demonstrations related to business planning, identification of halal products, and digital-based marketing strategies. Data were obtained through direct observation of student participation and documentation of the learning process. The results show that students gained a better understanding of halal edupreunership, as reflected in their ability to generate business ideas, recognize halal principles, and outline initial steps for simple business planning. Additionally, the activity increased students’ motivation to explore small-scale creative businesses rooted in Islamic values and encouraged them to utilize social media as a promotional tool. This community service program demonstrates that structured edupreunership instruction effectively strengthens halal entrepreneurial literacy among students and contributes to the development of productive and independent character traits.